Faktor-Faktor yang Berhubungan dengan Cemaran Mikroba dalam Air Minum Isi Ulang pada Depot Air Minum Kota Makassar - Kasim, Khiki Purnawati; Setiani, Onny; Wahyuningsih, Nur Endah (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background: Water is an essential substance for human life and other living things. Instant paced lifestyle and the needs of the ever increasing drinking water, causing drinking water refill a new and inexpensive alternative, but still have to qualify based PERMENKES 492 in 2010. The result of Makassar City Health Departemen only 60% drinking water depot eligible coliform bacteria. Research goals to analyze factors associated with microbial contamination in drinking water refill Makassar. Methods: This study is an observational study with cross sectional sample of 87 depots in Makassar. Data were analyzed using the chi-square test to determine the relationship between variables. Results: The result showed as much as 39.08% of raw water and 52.87% AMIU ineligible microbiological quality (coliform and E. coli), whereas observations indicate the condition of instruments and processing 3.45%, 68.87% employee hygiene, and depot sanitation 4.6% are not eligible. Conclusion: The test result showed an associations between the microbial contamination of raw water conditions, p=0.017 and employee hygiene, p=0.007. Keywords : drinking water refills, refill depots, microbial contamination